The current state of digital manikins to support pain self-reporting: a systematic literature review - Syed Mustafa Ali; Danielle C. Mountain; Rebecca R. Lee; Darcy Murphy; Alessandro Chiarotto; David C. Wong; William G. Dixon; Sabine N. van der Veer (PAIN Reports)
Abstract. This systematic literature review aimed to explore the current state of digital manikins to support pain self-reporting and to explore the extent to which manikins had progressed along the translational pathway. We systematically searched six electronic databases using a combination of key words and MeSH terms for “pain” and “manikin” to identify original studies in English that used a digital pain manikin for collecting information from adults with any condition. We extracted and descriptively synthesised data on the characteristics of studies and digital pain manikins and mapped them to a stage of the translational pathway (ie, design, testing, metric validation, and diffusion). We screened 6,189 articles, of which we included 104. Articles reported on 31 unique digital pain manikins. Most studies were conducted in Europe (n = 60; 58%), recruited people with pain/painful conditions (n = 69; 66%) from clinical settings (n = 67; 64%). Of the 31 manikins, the majority were two-dimensional (n = 21; 68%) with a front and back body view (n = 18; 58%) and allowed users to draw their pain on any area of the manikin (n = 23; 74%). Most manikins were still in the development and testing stages (n = 23; 74%). Only eight (26%) had progressed fully through the translational pathway, taking between 7 and 20 years to go from early development to diffusion. We found a substantial number of mostly two-dimensional digital pain manikins reported on in the last decade. However, most were still at early stages of the translational pathway, with only few having progressed through to diffusion into research and health care settings.